Preparation of High-Density Nanocrystalline Bulk Selenium by Rapid Compressing of Melt - 胡云 苏磊 刘秀茹 孙振亚 吕世杰 袁朝圣 贾茹 沈如 洪时明 (Chinese physics letters, 2010)
The melt＇s solidification behavior of elemental selenium is investigated by a series of experiments including rapid compressing to 2.8 and 3.5 GPa within 20ms respectively, slow compressing to 2.8 GPa for 20 min and natural cooling at ambient pressure. Based on the x-ray diffraction, scanning electron microscope and transmission electron microscope results of the recovered samples, it is clearly shown that homogenous nanostructures are formed only by the rapid compression processes, and that the average crystal sizes are about 18.7 and 19.0 nm in the samples recovered from 2.8 and 3.5 GPa, respectively. The relative density of the nanocrystalline bulk reaches 98.17% of the theoretical value. It is suggested that rapid compression could induce pervasive nucleation and restrain grain growth during the solidification, which is related to fast supercooling, higher viscosity of the melt and lower diffusivity of atoms under high pressure.